2017
DOI: 10.1186/s40249-017-0274-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of low-dose computed tomography to assess pulmonary tuberculosis among healthcare workers in a tuberculosis hospital

Abstract: BackgroundAccording to the World Health Organization, China is one of 22 countries with serious tuberculosis (TB) infections and one of the 27 countries with serious multidrug-resistant TB strains. Despite the decline of tuberculosis in the overall population, healthcare workers (HCWs) are still at a high risk of infection. Compared with high-income countries, the TB prevalence among HCWs is higher in low- and middle-income countries. Low-dose computed tomography (LDCT) is becoming more popular due to its supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
0
19
1
Order By: Relevance
“…There were four studies examining active tuberculosis among health care workers in this review [ 66 , 69 , 71 , 72 ]. A study conducted in India reported a pulmonary tuberculosis incidence rate of 314 per 100,000 person-years among health care workers and that this was 1.86 times higher than that of the general population [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were four studies examining active tuberculosis among health care workers in this review [ 66 , 69 , 71 , 72 ]. A study conducted in India reported a pulmonary tuberculosis incidence rate of 314 per 100,000 person-years among health care workers and that this was 1.86 times higher than that of the general population [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in South Africa reported a tuberculosis incidence rate of 1985 per 100,000 person-years among health care workers, which was double the incidence of tuberculosis in the general population [ 69 ]. A study conducted in China used low-dose lung CT examinations to detect active tuberculosis, and reported that the incidence and prevalence rates of active tuberculosis in health care workers were >2.8 times and >4.1 times greater than that of the general population, respectively [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although computed tomography (CT) has been reported to be useful in LTBI screenings, it is not yet included in the guidelines, and cost and risk versus effectiveness should be considered [23][24][25][26][27][28]. LDCT has a lower radiation dose than high-resolution computed tomography (HRCT), which has been shown to be useful in TB contact screening [26,29]. In this study, we found that it is necessary to rule out the possibility of TB by performing LDCT at the time of LTBI examination as well as CXR for QFT-GIT-positive HCWs.…”
Section: Plos Onementioning
confidence: 99%
“…The other two patterns of TB lung infection spread, bronchogenic (bronchiolitis) and haematogenous (miliary TB), are well known [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%